Room temperature creep behavior of nanocrystalline Gd2Zr2O7 ceramic with grain size below 10 nm. Issue 18 (15th December 2020) - Wang, Haomin; Huang, Zhangyi; Deng, Jirui; He, Duanwei; Wang, Jun; Qi, Jianqi; Qingyuan wang,
Abstract: Creep behavior at room temperature was firstly observed in nanocrystalline Gd2 Zr2 O7 ceramic (NC-GZO) having an average grain size about 7.8 nm. The creep strain rate sensitivity of NC-GZO was calculated, and many dislocations can be observed in the strained region. The mechanism causing this room temperature creep behavior was associated with the dislocations slipping which most likely occurs though grain boundaries sliding.